2021
DOI: 10.1111/ppc.12830
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' perceptions of a patient safety culture: A descriptive and cross‐sectional study

Abstract: Purpose The aim of this study was to evaluate nursing students' perceptions of a patient safety culture in one university in Turkey. Design and Methods The sample of this descriptive cross‐sectional study consisted of 299 undergraduate nursing students. Data were collected by having participants complete the Patient Safety Culture Scale (PSCS) and a personal information form. Findings Participants' scores on the PSCS were found to be moderate, and no significant differences were found between participants' stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a study by Kong et al (14), a positive response for all six evaluated domains was below 55%, with "Stress recognition" being the best rated and "Safety climate" the worst. In a study by Çiftcioğlu et al (21), the safety score was found to be moderate, and the students rated "Care environment" and "Employee behaviour" the best and "Training of employees" the worst. However, it should be noted that in both studies other instruments were used to assess the perception of nursing students and their perception was not, as with nurses from Slovak studies (19,20), marked by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…In a study by Kong et al (14), a positive response for all six evaluated domains was below 55%, with "Stress recognition" being the best rated and "Safety climate" the worst. In a study by Çiftcioğlu et al (21), the safety score was found to be moderate, and the students rated "Care environment" and "Employee behaviour" the best and "Training of employees" the worst. However, it should be noted that in both studies other instruments were used to assess the perception of nursing students and their perception was not, as with nurses from Slovak studies (19,20), marked by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…Instruments measuring nursing students' perceptions of PSC were adapted versions of tools designed for nurses. Two of these instruments were modified for nursing education (Ortiz de Elguea et al, 2019;Walker et al, 2019), while the other two were used without modification (Çiftcioğlu et al, 2022;Kong et al, 2019). The instruments focusing on nursing students' competencies in PSC were developed based on a literature review (Ginsburg et al, 2012;Lee et al, 2014;Tella et al, 2015), and QSEN KSA competencies (knowledge, skills, attitudes) (Miller & LaFramboise, 2009;Piscotty et al, 2013;Sullivan et al, 2009), and two instruments were developed based on the Madigosky et al (2006) framework intended for medical students (Chenot & Daniel, 2010;Schnall et al, 2008).…”
Section: Description Of Basic Characteristics Of Instruments Measurin...mentioning
confidence: 99%
“…It may be associated with the fact that the patient safety culture is not adequately addressed in the course content in the institutions where the study was conducted or the lack of learning opportunities in the current curriculum. Çiftcioğlu et al 27 have reported that the patient safety culture of nursing students is at a moderate level. It has also been stated that an effective educational curriculum is essential to create a patient safety culture and that a safety culture should definitely be emphasized in the nursing curriculum.…”
Section: Pscse and Subscale Scores Of Nursing Studentsmentioning
confidence: 99%